The difference of blood pressure and arterial stiffness after intake of arabica and robusta coffee in controlled hypertension - Pikir, Budi S; Andrianto, Andrianto; A, Ford Ance (Folia Medica Indonesiana, 2017)
Potential mechanisms of caffeine promote large artery stiffness and associated with increased morbidity and mortality of cardiovascular disease. To find the difference of blood pressure and arterial stiffness after intake of arabica and robusta coffee in controlled hypertension, a quasi-experimental study was done enrolling 24 controlled hypertension and 24 normotensive subjects collected by purposive sampling. Subjects received ± 10,6 g caffeinated coffee in 150 ml water with crossover protocol twice in 5 days. The assessment of arterial stiffness by obtaining ultrasound 2D image of common carotid artery then was calculated with beta stiffness index. Blood pressure and arterial stiffness was measured before coffee intake and again at 30 to 60 minutes thereafter. In controlled hypertension, significant differences were found between initial systolic blood pressure (SBP), 30 and 60 minutes after arabica (p 0,002) and robusta (p 0,012) intake; between diastolic blood pressure (DBP), 30 and 60 minutes after of arabica (p 0,004) and robusta (p 0,025) oral administration; and between initial beta stiffness index, 30 and 60 minutes after arabica (p 0,018) oral administration. However, no significant difference was found between initial beta stiffness index, 30 and 60 minutes after robusta (p 0,104) oral administration. No significant difference was found in all variables after arabica and robusta intake. Significant differences were found in blood pressure after arabica or robusta intake and in arterial stiffness after arabica intake. However, no significant differences were found in arterial stiffness after robusta intake and in all variables after arabica and robusta intake.